Eco-friendly thinking toward mitigating the greenhouse effect applied to the alumina grinding process - Domingues, Bruno Biondo [UNESP]; Rodriguez, Rafael Lemes [UNESP]; Souza, Guilherme Guerra de [UNESP]; Ávila, Benício Nacif [UNESP]; Rodrigues, Matheus de Souza [UNESP]; Ribeiro, Fernando Sabino Fonteque; Rodrigues, Alessandro Roger; Sanchez, Luiz Eduardo de Angelo [UNESP]; Bianchi, Eduardo Carlos [UNESP]; Lopes, José Claudio [UNESP] (Springer Nature, 2023)
The grinding process manufactures parts with geometric and dimensional precision and surface finish. During the procedure, material removal requires high energy and generates heat in the cutting zone. The grinding of advanced ceramics, such as alumina (Al2O3, 97% purity), is even more complex and economically expensive due to its mechanical properties. Thus, cooling and lubrication techniques are needed to control temperatures. The conventional flood technique is currently the most used, but it has a high environmental impact combined with unhealthy chemical agents in the cutting fluid. As a result, cutting fluids are the inputs that pose the most significant risks and damage to the environment and human health. Applying atomized and pressurized cutting fluid directly to the cutting zone has shown manufacturing potential compared to the conventional flood technique to solve these problems. Despite this, the minimum quantity of lubricant (MQL) technique does not provide good thermal dissipation compared to traditional methods, requiring the inclusion of auxiliary systems. In addition, one of these techniques deals with adding different proportions of water to the mixture, aiming to improve the heat transfer of the process and minimize the phenomenon of clogging the surface of the grinding wheel. Thus, this study analyzed the performance of a diamond grinding wheel in the advanced process of ceramic grinding using different proportions of cutting fluid applied to the MQL system, as follows: MQL + Pure (Pure—100% cutting fluid), MQL + 50% (50% cutting fluid and 50% water), MQL + 25% (25% cutting fluid and 75% water), and MQL + 15% (15% cutting fluid and 85% water) compared to the flood technique. Thus, surface roughness, soil surface topography by confocal microscopy analysis, roundness error, diametral grinding wheel wear, G-ratio, grinding cost analyses, and CO2 pollution analyses were evaluated. In addition, MQL applications revealed fewer pollutants. Furthermore, they were more economical application conditions from the grinding cost analysis, making them a great eco-friendly alternative for use in the industrial sector.
Keywords: Advanced ceramic; Cutting fluid; Environment; Greenhouse effect; Grinding; MQL